Virus-Receptor Mediated Transduction of Dendritic Cells by Lentiviruses Enveloped with Glycoproteins Derived from Semliki Forest Virus - Froelich, Steven (Public Library of Science, 2011)
Lentiviruses have recently attracted considerable interest for their potential as a genetic modification tool for dendritic cells (DCs). In this study, we explore the ability of lentiviruses enveloped with alphaviral envelope glycoproteins derived from Semliki Forest virus (SFV) to mediate transduction of DCs. We found that SFV glycoprotein (SFV-G)-pseudotyped lentiviruses use C-type lectins (DC-SIGN and L-SIGN) as attachment factors for transduction of DCs. Importantly, SFV-G pseudotypes appear to have enhanced transduction towards C-type lectin-expressing cells when produced under conditions limiting glycosylation to simple high-mannose, N-linked glycans. These results, in addition to the natural DC tropism of SFV-G, offer evidence to support the use of SFV-G-bearing lentiviruses to genetically modify DCs for the study of DC biology and DC-based immunotherapy.